Improving the Children’s Speaking Ability through Role Playing Method - Khoiriyah, Khoiriyah (Indonesian Journal of Early Childhood Education Studies, 2017)
This paper describes that the children’s speaking ability does not appear suddenly, but through several stages, and it needs to be formed and nurtured from an early age. The children’s speaking ability can also be improved through a variety of ways including through method of role playing. This paper describes and explains the processes adopted to optimize the children’s speaking ability through role playing method. This paper is based on the results of a Classroom Action Research (CAR) conducted in Playgroup of Aisyiyah at Mangli, with the stages of planning, action, observation, and reflection. The Method of role playing improves children's speaking ability, as shown from the scores increasment in pre-cycle which reaches an average of 57, the first cycle of 64.5 and the second cycle of 75.75. The increasment of the speaking ability is followed by children’s attitude changes, are: unembarrassed, speaking expressively, daring to express opinions, expressing various questions, answering multiple questions, and fluently expressing ideas.